Pictorial snapshot of the different roles men and women play along the bean value chain in Africa - Nchanji, Eileen Bogweh (Pan-Africa Bean Research Alliance, 2018)
The socio-cultural, economic and political environment over time has shaped and is still re-shaping gender roles, participation, decision making and benefit sharing in farming households in Africa. The pictures below are a reflection of the labour division by women, men and youths on farm and at the household. Identifying the different roles played by all actors at the different hubs in the value chain will guide appropriate program designs and interventions aimed at reducing inequality and promoting inclusivity. Complemented with the right partnership, infrastructural support, human capital and environment, we will be able to close the gender gap in the bean value chain and agriculture as a whole.